Adaptasi Kesiapan Menikah - Anindita, Siti Mutia; Chintia Viranda; Anisa Oktavia (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2024)
The high divorce rate in Indonesia is often attributed to individuals’ lack of readiness to build a marital life. This study aimed to adapt the Marriage Readiness Questionnaire (MRQ) into Indonesian and assess its validity and reliability using the Rasch Model approach. The participants consisted of 192 unmarried men and women aged 18–40, selected through purposive sampling. The adaptation process followed the International Test Commission guidelines, including translation, back translation, expert review, and readability testing. The results indicate that the marriage readiness scale has excellent psychometric properties, with a Cronbach’s Alpha of 0.86, item reliability of 0.98, and person reliability of 0.81. Unidimensionality analysis confirmed that the scale measures a single psychological caonstruct. Of the 38 items tested, 35 were considered valid, while 3 require revision. Additionally, two items showed gender bias and should be refined in future research. These findings suggest that the adapted scale is a reliable and valid tool for assessing marriage readiness among Indonesians